EVALUATION AND ORIENTATION OF ACTIVITIES IN ELDERLY WITH SIGHTS TO THE CONTROL OF THE BALANCE (Fiep Bulletin - online, 2013)
The balance disturbs affect the social autonomy, reduce the daily activities for the predisposition to the falls, and raise the costs with the health treatment. The objective of this study was to develop a advised program as strategy of intervention in elderly with balance alterations. Methods 840 elderly (550 women and 290 men; 67.4 ± 6,03 years; 69,2 ± 12,62 kg; 1,57 ± 0,09 m) had been analyzed by means of the evaluation of flexibility (test to seat and to reach of Wells), the power and endurance of inferior members by means of the test “to seat and to raise in thirty seconds” and the level of the balance by means of the test “static balance”. The data had been compared through test of 2 (p 0,05). RESULTS: Through test of 2, the power showed a “p” elevated in relation to the balance (0,00000005), and a low “p” (0,140247) among the balance and flexibility. CONCLUSION: for this sample the study shows that flexibility did not have influence in the balance, but the power had the influence elevated in the levels of the balance. The sample that presents these deficiencies may suffer falls and possess greater susceptibility to suffer serious breakings. On the basis of the results, conclude that the sample needs a direct intervention that may be followed with or without permanent accompaniment, with purpose to revert or to minimize the riots of the balance, with indications of exercises and attitudes that favor mobility. Other works with this and other samples are recommended for the verification of the adhesion to the proposal and its effectiveness, mainly because the prevention of the event of the fall is necessary and it is considered a good behavior of practical and a point of service of quality for the elderly.
Keywords: Functional Assessment; Balance; Elderly